Comparative survival of cancer patients requiring Israeli permits to exit the Gaza Strip for health care: A retrospective cohort study from 2008 to 2017 - Bouquet, Benjamin; Barone-Adesi, Francesco; Lafi, Mohamed; Quanstrom, Kathryn; Riccardi, Federica; Doctor, Henry; Shehada, Walaa; Nassar, Juliana; Issawi, Sali; Daher, Mahmoud; Rockenschaub, Gerald; Rashidian, Arash (PLOS ONE, 2021)
Background Gaza has been under land, sea, and aerial closure for 13 years, during which time Palestinian patients from Gaza have been required to obtain Israeli-issued permits to access health facilities in the West Bank (including east Jerusalem), as well as in Israel and Jordan. Specific groups, like cancer patients, have a high need for permits due to lack of services in Gaza. The approval rate for patient permits to exit Gaza dropped from 94% in 2012 to 54% in 2017. We aimed to assess the impact of access restrictions due to permit denials/delays on all-cause mortality for cancer patients from Gaza referred for chemotherapy and/or radiotherapy. Methods This study matched 17,072 permit applications for 3,816 cancer patients referred for chemotherapy and/or radiotherapy from 1 January 2008 to 31 December 2017 with referrals data for the same period and mortality data from 1 January 2008 to 30 June 2018. We carried out separate analyses by period of first application (2008–14; 2015–17), in light of varying access to Egypt during these times. Primary analysis compared survival of patients according to their first referral decision (approved versus denied/delayed) using Kaplan-Meier method and Cox regression. Findings Mortality in patients unsuccessful in permit applications from 2015–17 was significantly higher than mortality among successful patients, with a hazard ratio of 1·45 (95% CI: 1·19–1·78, p<0.001), after adjusting for age, sex, type of procedure, and type of cancer. There was no significant difference in mortality risk for the two groups in the 2008–2014 period. Interpretation Limitations to patient access due to unsuccessful applications for permits to exit the Gaza Strip had a significant impact on mortality for cancer patients applying for chemotherapy and/or radiotherapy in the period 2015–17. The substantially higher number of annual unsuccessful permit applications from 2015, combined with severely limited alternatives to access chemotherapy and radiotherapy during these years, may be important factors to explain the difference in the impact of permits delays/denials between the two study periods.